Sistematización de la experiencia de intervención del diseño e implementación de un plan de comunicación, para planta central y personal administrativo en una empresa de lavanderías, en la ciudad de Quito en el año 2017. - Camacho Muñoz, María Belén (2018)
In this report, the experience of intervention in the design and implementation of a communication plan for the central plant and administrative staff in a laundry company in the city of Quito is systematized in 2017. An analysis of the methodological procedure is presented below carried out during the project, which was based on the mixed approach, due to the application of the survey and direct observation for the collection of information in the field. In this process, exchanges with the Human Talent Manager were important. Together with these techniques, a bibliographic review was carried out to support the systematization axis. The provision of the tools to the collaborators helped to diagnose the internal situation in relation to organizational communication, knowing that the main problems were in the satisfaction of the workers, in the limited functionality of the channels, in the limited flow of information, in the poor participation of employees in the communication process and the lack of spaces for feedback. Based on these weaknesses, a communication plan was developed and implemented. The intervention experience, based on the execution of the actions contained in the proposal, is systematized according to its justification, impacts and learning achievements from the assertive communication approach.